Development and Characterization of Recycled Polypropylene/Teak Wood Dust Composites for Sustainable Applications in the Automotive Components Industry: Thermal and Mechanical Properties - Oktariani, Erfina; Ahnaf, Armilia Ailsa; Christine, Rebecca; Arina, Herlin (Jurnal Riset Kimia, 2025)
Utilizing recycled plastics is a crucial strategy for reducing waste and developing sustainable materials. Most of the recycled polypropylene (PP) in the industry is from reprocessed scrap. In contrast, this study explores a more challenging feedstock: post-consumer water cups collected by waste pickers, representing an environmentally impactful pathway. The recycled PP was combined with teak wood dust, an abundant lignocellulosic byproduct, antioxidant additives (Irganox 1010, Irgafos 168), and polypropylene-grafted-maleic anhydride (PPgMA) as a coupling agent to produce composites for the potential automotive component industry. Teak wood dust was added at 0–20 wt% to evaluate its influence on the thermal and mechanical performances. Fourier-transform infrared (FTIR) analysis confirmed that recycled PP maintained the functional groups similar to virgin PP, supporting its recyclability. Differential scanning calorimetry (DSC) showed decreasing enthalpy of fusion (101 to 91 J/g) and crystallinity (48% to 44%), indicating the disruption of crystalline packing by teak wood dust filler. The composites exhibited improved flexural strength and modulus with increasing filler content, attaining maximum values of 56.2 MPa and 2,132.9 MPa at 20 wt%. However, Izod impact strength decreased from 564 J/m (0 wt%) to ~300 J/m (20 wt%), indicating a trade-off between stiffness and toughness. Despite this reduction, all composites exceeded the minimum Izod impact strength requirement for automotive polypropylene copolymers (≥75 J/m, SNI 8432:2022). Overall, this study highlights the feasibility of valorizing both post-consumer plastic waste and wood dust into functional, sustainable composites for automotive components.